1990
DOI: 10.1093/oxfordjournals.humrep.a137205
|View full text |Cite
|
Sign up to set email alerts
|

A survey of public attitudes toward oocyte donation between sisters

Abstract: Oocyte donation offers the possibility of pregnancy for many patients with premature ovarian failure (POF) and recently a number of patients have been requesting egg donation by a sister. While patients anxious to achieve a pregnancy are favourably disposed toward egg donation, the existence of favourable attitudes in others, and thus the amount of social support such patients will receive, depends upon the wider social environment. A survey of public opinion was conducted utilizing a random sample of 501 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The present study revealed that 52% of female students studied showed a positive attitude towards oocyte donation. This a rms earlier studies which showed that about 50-90% of non-patient respondents exhibit a positive attitude towards oocyte donation [20][21][22][29][30][31]. In contrast, a few studies in Africa have reported poor attitude towards egg donation [12,32].…”
Section: Discussionsupporting
confidence: 75%
“…The present study revealed that 52% of female students studied showed a positive attitude towards oocyte donation. This a rms earlier studies which showed that about 50-90% of non-patient respondents exhibit a positive attitude towards oocyte donation [20][21][22][29][30][31]. In contrast, a few studies in Africa have reported poor attitude towards egg donation [12,32].…”
Section: Discussionsupporting
confidence: 75%
“…(10, 11) Authors have surmised that in a patriarchal society where children inherit the father's name, maternal relatedness in less important. (4, 12,13)…”
Section: Discussionmentioning
confidence: 99%
“…The ethical problems that prompted the October 2005 change in policy guidelines included the commercialization of egg donation, the excessive ovarian stimulation necessary to increase oocyte yield, and the potential for infectious disease transmission. It must also be noted that the difference in chances for them to become pregnant may cause an uneasy feeling between donor and receiver [8,9]. Although patients received extra medical care for donating eggs at our Center, their donation was purely humanitarian and involved no monetary compensation.…”
Section: Discussionmentioning
confidence: 99%